Caring for Family Members Older Than 50 Years of Turkish and Northwest African Descent: The Meaning of Caregiving. Issue 1 (January 2016) - van Eechoud, Ineke J.; Grypdonck, Mieke; Leman, Johan; Van Den Noortgate, Nele J.; Deveugele, Myriam; Verhaeghe, Sofie
Abstract : Background: The first generation of immigrants to Belgium from Turkey and Northwest Africa are aging and at risk for developing cancer. Family members play an important role in both illness and old age. Objective: The objective of this study was to gain insight into experiences and perceptions of families with Turkish or Northwest African backgrounds who were caring for cancer patients older than 50 years in Flanders, Belgium. Methods: A qualitative research design with elements of constructivist grounded theory was used. Twenty-eight loosely structured interviews were conducted. Three researchers were involved in data analysis (researcher triangulation), and 6 conversations took place with experts. Results: Cancer appeared to be a family matter. Caregiving had a strong moral meaning for all participants, particularly for children providing care to a parent. Caregiving could be described as "guiding": family members led the patient through, or familiarized the patient with, the healthcare system. There were strong differences in the extent to which family members believed they should provide care, as well as the kind of professional care considered desirable. Conclusions: Despite shared values of the importance of family and family caregiving, concrete ideas about caregiving differed considerably. The findings imply that shared cultural or religious normative values do not predict day-to-day care practices. Implications for Practice: This study provides new insights into the moral and practical meaning of caregiving, which will help professionals understand the roles adopted by family members. Furthermore, individualized approaches to care appear to be essential, because concrete ideas about informal caregiving differ strongly despite shared values.